Design of industrial robot sorting and assembly control system based on Profinet bus - Zhang, Yang; Wang, Tao (Frontiers in Mechanical Engineering, 2025)
IntroductionIn complex industrial environments, traditional industrial robot control systems are difficult to meet the requirements of automated production for industrial parts sorting and assembly tasks.MethodsFor this purpose, this study constructs an industrial robot sorting and assembly control system based on Ethernet bus. Its innovation lies in the deep coupling of Profinet real-time Ethernet with self‐tuning fuzzy PID control, compressing communication jitter to the sub‐millisecond level. Introduce the greedy visual hybrid algorithm; A four-layer integrated framework of “hardware ‐ communication ‐ algorithm ‐ human-machine” has been constructed, which can directly reuse the existing Siemens PLC and I/O ecosystem, significantly reducing deployment costs.ResultsThe experimental results show that when the time of the fusion control algorithm is 4.0 seconds, the position tracking deviation is 0.012mm. The position tracking deviation of the deep deterministic policy gradient algorithm is 0.018mm, and its performance is inferior to that of the fusion algorithm. The sorting recall rate of the fuzzy sliding mode industrial sorting and assembly control system is 93.67%, which is lower than that of the fusion control system.DiscussionThe research findings provide a reusable technical paradigm for the next generation of highly flexible and scalable intelligent production lines, which are expected to be rapidly implemented in scenarios such as micro-nano electronic assembly, flexible pharmaceuticals, and circular remanufacturing.